2020
DOI: 10.3390/biom10010109
|View full text |Cite
|
Sign up to set email alerts
|

Production of Polyhydroxyalkanoates by Two Halophilic Archaeal Isolates from Chott El Jerid Using Inexpensive Carbon Sources

Abstract: The large use of conventional plastics has resulted in serious environmental problems. Polyhydroxyalkanoates represent a potent replacement to synthetic plastics because of their biodegradable nature. This study aimed to screen bacteria and archaea isolated from an extreme environment, the salt lake Chott El Jerid for the accumulation of these inclusions. Among them, two archaeal strains showed positive results with phenotypic and genotypic methods. Phylogenetic analysis, based on the 16S rRNA gene, indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The present study is a continuity of our previous work [ 9 ], proposing the possibility to enlarge our knowledge about PHB secretion by a large number of haloarchaeal strains from Chott El Jerid due to their several advantages: firstly, their growth at high salinity minimized microbial contamination. Secondly, the high osmotic pressure in their cells facilitated the PHB recovery.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…The present study is a continuity of our previous work [ 9 ], proposing the possibility to enlarge our knowledge about PHB secretion by a large number of haloarchaeal strains from Chott El Jerid due to their several advantages: firstly, their growth at high salinity minimized microbial contamination. Secondly, the high osmotic pressure in their cells facilitated the PHB recovery.…”
Section: Discussionmentioning
confidence: 76%
“…Later, Han et al [ 30 ] confirmed the detection of phaEC genes in 18 PHB or poly(3-hydroxybutyrate-co-hydroxyvalerate) PHBV producers, including Haloarcula , Halorubrum , Natrinema , and other genera by utilizing carbohydrates either glucose or fructose [ 30 ]. More recently, it was reported that these two genes were detected in the genome of Natrinema altunense CEJGTEA101, isolated from Chott El Jerid [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations